The effect of skill-based physical exercises using specific endurance on a number of physical variables of young football players - Yousef, Asst. Prof. Dr. Falah Abdul Hassan; Abdullah, Asst. L. Haitham Munim Ajami (Sulaimani Journal for Humanities, 2026)
The researchers addressed the importance of specific endurance as one of the most important factors affecting the level of player performance during the two halves of the match. "A player with substandard specific endurance faces a greater oxygen debt, which leads to slower recovery and early fatigue." On the other hand, there is a correlation between the extent of a player's mastery of football tactics and techniques and the level of development of his specific endurance. Improving the economy of effort exerted to perform a skill reduces the amount of energy required, which requires that the player only perform the movements necessary to control the ball and act appropriately to the game situation. The research population consisted of the youth of Naft Al-Wasat Football Club for the (2024-2025) football season, totaling (30) players. The research sample consisted of (20) players, representing (66.66%) of the research population. The sample was divided into two groups (experimental and control) by following the method of random selection using a lottery, with (10) players in each group. The researcher ensured that all players in the research sample were under 19 years of age. The pilot study sample, consisting of seven players, was excluded from the research sample, as were the three goalkeepers. Conclusions: 1- Skill-based physical exercises using specific endurance techniques led to the development of all physical variables (speed endurance, leg strength endurance, leg explosive power, leg speed-strength, transitional speed, agility, and general endurance), as demonstrated by comparing the pre- and post-test results of the experimental group. 2- The training program developed by the coach led to the development of some physical variables (leg explosive power, agility, and general endurance), as demonstrated by comparing the pre- and post-test results of the control group. Recommendations: 1- Skill-based physical exercises using specific endurance techniques can be used in training young football players. 2- Low-intensity interval training can be used to develop specific endurance in football players.
Keywords: Physical and skillbased exercises; endurance exercises; football players